Enhancing Tenth Graders’ Speaking Ability through Quiz-Quiz Trade at SMA PGRI 1 Palembang - Muhammad Kamal; Gaya Tridinanti; Jenny Elvinna Manurung (Didascein : Journal of English Education, 2026)
This study focuses on the application of the Quiz-Quiz Trade Technique to assist tenth-grade students in improving their speaking ability. The Quiz-Quiz Trade Technique is a cooperative learning strategy that provides opportunities for students to engage in speaking practice. The objective of this study was to determine the substantial enhancement in speaking abilities by using the Quiz-Quiz Trade Technique among tenth graders at SMA PGRI 1 Palembang, as well as to examine the difference in speaking skills between students taught with this technique and those who were not. This study employed a quasi-experimental design. The population consisted of tenth-grade students at SMA PGRI 1 Palembang during the academic year 2024-2025. Purposive sampling was used to select 70 students, divided into two groups: the experimental group and the control group, each comprising 35 students. Data were gathered through speaking tests conducted twice. The data analysis used a paired-sample t-test and an independent-samples t-test. The paired-sample t-test results indicated a significant improvement in the speaking ability of the tenth graders using the Quiz-Quiz Trade technique. The results of the study showed a significant improvement in students' speaking skills in the experimental group compared to the control group. The independent sample t-test results revealed a significant difference in speaking skills between the students who received instruction using the Quiz-Quiz Trade technique and those who did not.